Reducing Red Tape’s Negative Consequences for Leaders: The Buffering Role of Autonomous Motivation - Muylaert, Jolien; Bauwens, Robin; Audenaert, Mieke; Decramer, Adelien (Frontiers in Psychology, 2022)
In a context where the amount of red tape in healthcare organizations continues to rise, head nurses’ job satisfaction is constantly under pressure. By building on the Job Demands-Resources model, we developed a theoretical model investigating the relationship between red tape and job satisfaction. By investigating the mediating role of discretionary room and the moderating role of autonomous motivation in this relationship, this study does not only aim to provide additional knowledge regarding the underlying mechanisms in this relationship, but also to increase our understanding of how this suffering at work can be mitigated. Our conditional process analyses (N = 277 head nurses) indicate that red tape undermines head nurses’ job satisfaction and that discretionary room acts as an underlying mechanism in this process. By revealing the mediating role of discretionary room, this study advances our understanding of the risks originating from red tape for leaders. Furthermore, our findings also indicate that autonomous motivation mitigates the negative relation between red tape and discretionary room and between red tape and job satisfaction. As autonomous motivation turns out to be an important protection mechanism against the negative consequences of red tape, organizations should put extra effort into stimulating the autonomous motivation of their leaders. When organizations make sure that their leaders’ job designs and work environments meet the need for autonomy, competence, and relatedness, leaders will become more autonomously motivated, which will buffer the negative impact of red tape.